On the Influence of Vanadium on Air‐Hardening Medium Manganese Steels for Sustainable Forging Products. Issue 6 (3rd June 2021) - Gramlich, Alexander; Middleton, Aaron; Schmidt, Rolf; Krupp, Ulrich
Abstract : Sustainable forging steels must be evaluated according to their performance within the circular product economy, which encompasses efficient manufacturing, enhanced longevity and improved recycling rates of constituent ferroalloys. This research, article number 2000592, by Alexander Gramlich and co‐workers, focused on developing vanadium alloyed air‐hardening medium manganese steels, that could achieve high through‐hardness with good tempering resistance, which can enable down‐stream productivity savings.